The Protective Influence of Bilingualism on the Recovery of Phonological Input Processing in Aphasia After Stroke - De Letter, Miet; Cocquyt, Elissa-Marie; Cromheecke, Oona; Criel, Yana; De Cock, Elien; De Herdt, Veerle; Szmalec, Arnaud; Duyck, Wouter (Frontiers in Psychology, 2021)
Language-related potentials are increasingly used to objectify (mal)adaptive neuroplasticity in stroke-related aphasia recovery. Using preattentive [mismatch negativity (MMN)] and attentive (P300) phonologically related paradigms, neuroplasticity in sensory memory and cognitive functioning underlying phonological processing can be investigated. In aphasic patients, MMN amplitudes are generally reduced for speech sounds with a topographic source distribution in the right hemisphere. For P300 amplitudes and latencies, both normal and abnormal results have been reported. The current study investigates the preattentive and attentive phonological discrimination ability in 17 aphasic patients (6 monolinguals and 11 bilinguals, aged 41–71 years) at two timepoints during aphasia recovery. Between the two timepoints, a significant improvement of behavioral language performance in both languages is observed in all patients with the MMN latency at timepoint 1 as a predictive factor for aphasia recovery. In contrast to monolinguals, bilingual aphasic patients have a higher probability to improve their processing speed during rehabilitation, resulting in a shortening of the MMN latency over time, which sometimes progresses toward the normative values.